Cameroon : Social Safety Nets - World Bank (Washington, DC, 2012)
This report responds to the Government of Cameroon's strong interest in strengthening its social safety net system to support the poorest and most vulnerable households during crises. It is grounded in extensive discussions with government counterparts in a collaborative and inclusive process. The report incorporates detailed comments received from the government as well as important donors and partners through two participatory stakeholder workshops. In addition, it is a part of the World Bank's rapid social response program to support the Government of Cameroon in making its system of safety nets more comprehensive, flexible, and suitable to the country's economic and social conditions. In this context, the objective of this report is to lay the ground for a social safety net system that can address the needs of the poor in Cameroon. The high level of chronic poverty and high levels of malnutrition (especially in the northern regions of the country) call for targeted social safety net program. Therefore, the objective of this report is to: (i) assess the evolution and extent of poverty levels; (ii) provide a detailed, updated inventory of existing social safety net programs; (iii) identify their shortcomings; and (iv) propose suggestions, based on international experience, for improving the coverage, efficiency, relevance and financial sustainability of the most relevant programs to set the basis for a coherent safety net system.